2015
DOI: 10.4178/epih/e2015001
|View full text |Cite
|
Sign up to set email alerts
|

Effect change of obesity on diabetes depending on measurement: self-reported body mas index from 2012 Community Health Survey vs. directly measured from the Korea National Health and Nutrition Examination Survey

Abstract: OBJECTIVES:Obesity is a well-recognized risk factor for type 2 diabetes mellitus (DM) among young and middle-aged adults in South Korea. To elaborate on the association between obesity and Diabetes mellitus (DM), subjective data from self-reporting survey or objective data from health examination is generally used. This study was conducted to validate the change of association from using these different measurements.METHODS:Community Health Survey data and Korea National Health and Nutrition Examination Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This was because overestimation of height increased with age while weight was underestimated in males in their 20s and 30s and females in their 20s to 40s in KCHS [16]. In a study investigating the effects of prevalence of obesity on diabetes according to method of survey in adults aged 45 years or older, the difference of obesity prevalence by questionnaire in KCHS and that by physical examination in KNHANES was 6.4%p and the difference of diabetes prevalence was 2.6%p [17]. Other study also reported that self-reported data and actually measured data differ particularly according to sex [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was because overestimation of height increased with age while weight was underestimated in males in their 20s and 30s and females in their 20s to 40s in KCHS [16]. In a study investigating the effects of prevalence of obesity on diabetes according to method of survey in adults aged 45 years or older, the difference of obesity prevalence by questionnaire in KCHS and that by physical examination in KNHANES was 6.4%p and the difference of diabetes prevalence was 2.6%p [17]. Other study also reported that self-reported data and actually measured data differ particularly according to sex [18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, this study clearly has strengths as well. Compared to similar Korean studies [16,17], we performed a more comprehensive comparison using six and eight variables in KCHS and KNHANES, respectively, over six years, and also analyzed the differences of estimates according to method of survey by comparing estimates taken from interviews and estimates taken from physical examinations data. Furthermore, we analyzed the time series stability of subgroup estimates and demonstrated that subgroup estimates might differ between the two surveys even with little differences in yearly estimates overall.…”
Section: Discussionmentioning
confidence: 99%